Export sales of U.S. beef semen increased faster than domestic semen sales - Sandra K. Johnson; Kevin C. Dhuyvetter (Kansas Agricultural Experiment Station Research Reports, 2011)
The use of artificial insemination (AI) in the dairy industry grew tremendously in the 1940s and has since become the industry norm. Adoption of AI in the beef industry has been much slower largely due to the more extensive nature of beef production systems. Improvements in protocols to synchronize estrus and ovulation now allow beef producers to achieve high pregnancy rates to AI with no heat detection and value-driven marketing programs have provided more incentive for use of high-accuracy genetics. The 2007 USDA National Animal Health Monitoring Surveillance survey reports the proportion of beef operations that use AI is only 7.6%. However, adoption of AI in herds of 200 head or greater was 19.8% compared to 5.6% and 8.4% for herd sizes of 1 to 49 and 50 to 99 head, respectively, indicating larger operations are more likely to adopt this technology. Little information is available concerning changes in semen use over time in the beef industry and what this may reflect about the adoption of AI by beef producers. The purpose of this study was to examine trends in domestic, custom frozen, and export sales of semen over time and how these trends relate to beef feeder calf prices and cow inventories.
Keywords: Kansas Agricultural Experiment Station contribution; no. 11-171-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1047; Cattlemen& #x27; s Day; 2011; Beef; Domestic semen; Artificial insemination (AI); Sales